Improvement of Performance in Energy Systems from Renewable Sources Based on Green Hydrogen - Yacine BENCHENINA; ENCA/Abderrahim ZEMMIT (Université Mohamed Boudiaf - M’Sila, 2025)
This dissertation aims to improve the performance of renewable energy systems based on green hydrogen, emphasizing its pivotal role in supporting decarbonization efforts and enhancing energy security in Algeria. Amid a global transition towards sustainable energy sources to tackle climate change and dwindling fossil fuel reserves, green hydrogen emerges as an innovative energy carrier, offering a clean and efficient alternative to traditional fuels. The study capitalizes on Algeria’s abundant natural resources, particularly photovoltaic solar energy, highlighting the country’s significant potential to become a key player in the global green hydrogen economy. The research employs advanced modeling and simulation tools (such as HOMER Pro and MATLAB Simulink) to assess photovoltaic productivity, electrolysis performance, and fuel cell efficiency under diverse operating conditions. Additionally, the study explores the feasibility of utilizing seawater electrolysis and wastewater treatment as sustainable water sources for hydrogen production, thereby enhancing the economic and environmental viability of the projects. The first chapter examines the global energy crisis and the innovative role of green hydrogen. The second chapter provides a comprehensive review of international and regional research on green hydrogen production, underscoring the importance of international collaboration to boost this sector in Algeria. The third chapter focuses on the technical, economic, and environmental challenges, offering innovative solutions to optimize the performance of energy systems based on green hydrogen. The findings reveal promising opportunities for diversifying Algeria’s economy, strengthening energy security, and creating new jobs, in line with Algeria’s international commitments to combating climate change. This study bridges the gap between theoretical research and practical application, paving the way for a resilient, low-carbon, and sustainable energy future. Date soutenance : 22/04/2025